Self-regulated learning as a predictor of learning outcomes in physical education: a systematic literature review - Noviani Noviani; Nuridin Widya; Hendri Neldi; Atradinal Atradinal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to systematically examine the role of self-regulated learning (SRL) as a predictor of learning outcomes in physical education, focusing on the strength and consistency of its influence across different educational contexts. A systematic literature review was conducted following PRISMA 2020 guidelines, using Scopus, Web of Science, and Google Scholar databases with a defined search period from 2020 to 2025. Empirical studies employing quantitative or mixed-method designs were included, and data were extracted and synthesized using a thematic approach to identify patterns, relationships, and variations in findings. The results indicate that SRL components such as goal setting, self-monitoring, and self-reflection consistently show positive associations with learning outcomes, including skill performance, motivation, and physical literacy, although the strength of relationships varies across studies. Some inconsistencies and methodological differences were also identified. These findings suggest that SRL plays a significant role in physical education learning, while highlighting the need for more robust and longitudinal research to strengthen causal interpretations.